Immersive VR and Education: Embodied Design Principles That Include Gesture and Hand Controls - Johnson-Glenberg, Mina C. (Frontiers in robotics and AI, 2018)
This article explores relevant applications of educational theory for the design of immersive virtual reality (VR). Two unique attributes associated with VR position the technology to positively affect education: (1) the sense of presence, and (2) the embodied affordances of gesture and manipulation in the 3rd dimension. These are referred to as the two profound affordances of VR. The primary focus of this article is on the embodiment afforded by gesture in 3D for learning. The new generation of hand controllers induces embodiment and agency via meaningful and congruent movements with the content to be learned. Several examples of gesture-rich lessons are presented. The final section includes an extensive set of design principles for immersive VR in education, and finishes with the which are hypothesized to optimize the pedagogy within a lesson.